Factors associated with knowledge on the spread of HIV/AIDS among Secondary School Students of Groupe Scolaire De Rugando in Kigali City, Rwanda. - Nwankwo, Chinenye Mercy; Uwizeye, Denyse Sibomana (Kabale University, 2024)
Human Immunodeficiency Virus has continued to spread in most countries, including Rwanda. Youths are particularly vulnerable to HIV/AIDS because they are not sufficiently prepared to address problems related to their sexuality and also because they do not have enough real knowledge about HIV and AIDS. The study assessed factors associated with knowledge of the spread of the Human Immunodeficiency virus (HIV) among students of Groupe Scolaire de Rugando in Kigali City, Rwanda. The study adopted a descriptive cross-sectional approach among the target population of 950 students in the secondary school of Groupe Scolaire de Rugando. About 108 students were randomly selected using the systematic sampling method. Self-administered structured questionnaires were used for data collection for one month with the help of a trained research assistant. The study instrument was pilot-tested in a mission secondary school outside the study population and further validation was carried out before it was administered based on consent. The most common predisposing factors in the study to adolescents to HIV/AIDS were curiosity and the need to experiment. The study findings showed that 78% accepted that HIV is transmitted by engaging in unprotected sexual intercourse with an infected person, 65% accepted that the presence of other sex partners increases the risk of contracting HIV, 69% accepted that regular use of condoms helps to reduce the risk of contracting HIV and 55% accepted that by reducing the number of sexual partners, chances of HIV infection are reduced. Additionally, 44 (43.14%, C. I.: 33.37-53.32) of the students indicated that they had previously engaged in sex, while 58 (56.86%, C. I: 46.68-66.63) showed that they did not engage in sexual practice. The majority of the students who had engaged in sex had never used a condom (59.09%). The usage of condoms was perceived by respondents that it does not allow their partner to enjoy sex. This study recommends the need to design interventions that aim to raise awareness of the negative consequences of risky sexual behaviors; increase the availability and accessibility of condoms; fight against the entry of drugs into the country as well as their circulation and accessibility to the youth and finally, guidance and counseling services should be introduced in schools.